2007
DOI: 10.1007/s00114-007-0263-x
|View full text |Cite
|
Sign up to set email alerts
|

Soil and preen waxes influence the expression of carotenoid-based plumage coloration

Abstract: The signaling function of carotenoid-based plumage is mainly determined by the concentration of pigments in feathers. For this reason, most studies of the proximate control of coloration focus on processes during and preceding moult. In great tits Parus major, past research demonstrates that carotenoid-based plumage coloration honestly indicates male quality and, thus, may be a sexually selected signal. In this study, we investigate how dirt and preen oil influence the coloration of carotenoid-based feathers i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
1
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 30 publications
1
36
1
1
Order By: Relevance
“…Second, birds inhabiting air-polluted areas may have to invest more heavily in preening. In conclusion, even if feather colours are often viewed as a fixed trait following moult, our results conjointly with studies on other bird species (Örnborg et al 2002;Moyer et al 2003;Zampiga et al 2004;Delhey et al 2006) suggest that plumage colourations can change, and soiling seems to be an important factor to affect this change (Montgomerie 2006a;Surmacki & Nowakowski 2007;Lenouvel et al 2009). Much work remains to determine the role of air pollution and aerosol particles in altering plumage colourations.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…Second, birds inhabiting air-polluted areas may have to invest more heavily in preening. In conclusion, even if feather colours are often viewed as a fixed trait following moult, our results conjointly with studies on other bird species (Örnborg et al 2002;Moyer et al 2003;Zampiga et al 2004;Delhey et al 2006) suggest that plumage colourations can change, and soiling seems to be an important factor to affect this change (Montgomerie 2006a;Surmacki & Nowakowski 2007;Lenouvel et al 2009). Much work remains to determine the role of air pollution and aerosol particles in altering plumage colourations.…”
Section: Discussionsupporting
confidence: 79%
“…A study on budgerigars, Melopsittacus undulatus, in which dirtiness was artificially induced, also showed that preening is effective in removing soiling from plumage and increasing its colour reflectance, and that this effect was particularly pronounced in the UV range (Zampiga et al 2004). The effect of soiling on structural, short wavelength feather colours, however, is not general, as other studies, which employed different methodological approaches, obtained contrasting results (Montgomerie 2006a;Surmacki & Nowakowski 2007;Lenouvel et al 2009). One of these studies assessed the effect of dirt accumulation on the feathers of bird museum specimens (Montgomerie 2006a).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…By measuring plumage reflectance before and after cleaning feathers with a mild detergent, he revealed that dirt lowered spectral reflectance, mainly in the range between 400 and 700 nm. In a similar study, Surmacki and Nowakowski (2007) cleaned the yellow (carotenoid-based) feathers of great tits, Parus major, with chloroform-methanol mixture which increased feather brightness and shifted hues towards longer wavelengths. Unfortunately, both of these studies did not separate the relative importance of soling and preen waxes on color change, because due to the cleaning method, both agents were removed simultaneously.…”
Section: Introductionmentioning
confidence: 95%